EDUKASI BEYOND USE DATE (BUD) DAN PEMANFAATAN INFUSED WATER KURMA-JERUK NIPIS SEBAGAI UPAYA PREVENTIF ANEMIA PADA SISWA/I SMA SANTO YOSEPH MEDAN - Fitri Wahyu Dhini; Hazimah (INSTITUT KESEHATAN DELI HUSADA, 2026)
Anemia remains a public health problem in Indonesia, particularly among adolescent girls, with a prevalence of 48.9% according to the 2018 Basic Health Research (Riskesdas). Anemia impacts learning concentration, productivity, and quality of life. Furthermore, a lack of public understanding of medication's Beyond Use Date (BUD) has the potential to lead to medication errors. This Community Service Program (PKM) aims to provide education about medication BUD and introduce date-lime infused water as a preventative measure for anemia. The activity was conducted with eleventh-grade students at Santo Yoseph High School in Medan. Methods used included counseling, demonstrations, and discussions. It is hoped that this activity will increase adolescents' knowledge and awareness of the safe use of medications and their iron intake to prevent anemia.